2006
DOI: 10.1029/2005jd006415
|View full text |Cite
|
Sign up to set email alerts
|

Negative cloud‐to‐ground lightning properties from high‐speed video observations

Abstract: [1] From analysis of digital high-speed video records of 233 negative cloud-to-ground (CG) lightning flashes associated with 27 thunderstorms in southeastern Brazil, various lightning properties have been determined. The analysis of the video records showed that although 20% of them were single-stroke flashes and the average number of strokes per flash was 3.8, a significant variation was observed in these parameters from storm to storm. In a smaller subset containing 138 flashes, 70 (51%) had multiple termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
91
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 23 publications
19
91
5
Order By: Relevance
“…The highest probability (64 %) is for single-stroke flashes, with 19 % having two strokes, 9 % having 3 strokes and much lower percentages with higher multiplicity values. The distribution is markedly different than reported in accurate stroke count studies in Brazil (Saba et al, 2006) and Arizona (Saraiava et al, 2010), where the average multiplicity was 3.9. Fleenor et al (2009) studied storms in the US mid-planes and reported a video multiplicity average of 2.83 with median 2 for 103 strokes.…”
Section: Methodology and Resultscontrasting
confidence: 45%
“…The highest probability (64 %) is for single-stroke flashes, with 19 % having two strokes, 9 % having 3 strokes and much lower percentages with higher multiplicity values. The distribution is markedly different than reported in accurate stroke count studies in Brazil (Saba et al, 2006) and Arizona (Saraiava et al, 2010), where the average multiplicity was 3.9. Fleenor et al (2009) studied storms in the US mid-planes and reported a video multiplicity average of 2.83 with median 2 for 103 strokes.…”
Section: Methodology and Resultscontrasting
confidence: 45%
“…The majority of CG flashes over Brazil are negative flashes (Saba et al, 2006). Depending on different wind regimes, varying lightning activity has been observed over the Amazon region.…”
Section: Transport Modelling: Flexpartmentioning
confidence: 99%
“…A large fraction of charge is lowered to the ground within a "return stroke," an intense discharge region that propagates up the stepped leader path from ground to cloud. A flash consists of one or more strokes closely spaced in time travelling along the same discharge channel (Thery, 2001;Saba et al, 2006a). The first stroke is often the most energetic one and assumed to produce the largest amount of LNO x (Hill, 1979;Dawson, 1980).…”
Section: Lightningmentioning
confidence: 99%